Pengaruh Oikumene di Indonesia Ditengah Multidimensi Gereja Masa Kini - Lestari Loi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article explores the impact of ecumenism in Indonesia in the context of the increasingly widespread and complex development of the modern church. Ecumenicalism, as an ecumenical movement that prioritizes unity between Christian churches, plays a vital role in forming relations between denominations amidst the rich diversity that exists. In facing ever-changing social and political dynamics, churches in Indonesia are faced with various challenges in implementing their mission. However, behind these challenges, opportunities arise to unite in an effort to serve the community. In the midst of this reality, ecumenism opens up space for dialogue between denominations, emphasizing the importance of unity in diversity, social solidarity and the development of spirituality. With a multidimensional approach, churches in Indonesia are not only faced with internal issues, but are also expected to be able to make a more significant contribution in building a harmonious and inclusive society. This article concludes that ecumenicalism in Indonesia not only strengthens ties between churches, but also has a positive impact on social life and diversity in this country.